2014
DOI: 10.4103/1755-6783.154825
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis A virus infection in different age groups of children

Abstract: Context: Hepatitis A is one of the most common causes of hepatitis in the pediatric age group and the most common cause of fulminant hepatic failure (FHF) among children in India. Hepatitis A is a waterborne disease. High endemicity obviates the need for vaccine in the community. Aims: We studied 116 children in the outpatient department (OPD) to know the seroprevalence of hepatitis A virus (HAV), total antibodies, and the effect of various demographic and water sanitation variables on it. Settings and Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
3
0
3
Order By: Relevance
“…Low endemicity regions are high-income countries with good sanitation and hygienic conditions (infection rates are low, i.e., < 50% by age 30 years). Due to poor sanitary conditions and access to clean water, most of the population in developing countries is infected in early childhood (i.e., seroprevalence up to about 90% in children), classifying the regions as highly endemic [1, 6]. In some countries, like India, parts of the populations have recently undergone rapid socioeconomic development, which may have an impact on endemicity shift and the resulting burden of disease [1].…”
Section: Introductionmentioning
confidence: 99%
“…Low endemicity regions are high-income countries with good sanitation and hygienic conditions (infection rates are low, i.e., < 50% by age 30 years). Due to poor sanitary conditions and access to clean water, most of the population in developing countries is infected in early childhood (i.e., seroprevalence up to about 90% in children), classifying the regions as highly endemic [1, 6]. In some countries, like India, parts of the populations have recently undergone rapid socioeconomic development, which may have an impact on endemicity shift and the resulting burden of disease [1].…”
Section: Introductionmentioning
confidence: 99%
“…9 According to the World Health Organization (WHO) position paper 10 published in 2012, transition from high to intermediate endemicity of hepatitis A leads to increased risk of clinically significant hepatitis. Overall, epidemiological data, difficulty in diagnosis of infection in small children due to asymptomatic nature or non-specific symptoms, 4 and risk of disease severity with increasing age underline the importance of prevention of hepatitis A in the community.…”
Section: Epidemiological Shift I N Pattern O F Hepatitis Amentioning
confidence: 99%
“…3 Another study reported higher seroprevalence in rural and urban areas (90.9 vs 77.1%, respectively) and children from all socioeconomic strata (lower social class 87.2% vs higher social class 54.5%). 4 Hepatitis A virus is transmitted through fecooral route and represents an important cause of acute viral liver disease and most common cause of fulminant hepatic failure among children in India, 4 which can be life-threatening. The coexistence of heterogeneous pockets of exposed and unexposed individuals in different social classes and regions within country makes population prone for outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Çocuklarda hastalık kronikleşme olmaksızın iyi prognoza sahiptir. En korkulan komplikasyonu akut karaciğer yetmezliğidir (1,2).…”
Section: Introductionunclassified
“…Çocuklarda hastalık kronikleşme olmaksızın iyi prognoza sahiptir. En korkulan komplikasyonu akut karaciğer yetmezliğidir (1,2). Hepatit B virüsü (HBV) ve hepatit C virüsü (HCV) enfeksiyonları, asemptomatik enfeksiyondan siroza ve hepatoselüler karsinomaya kadar geniş klinik spektrumda olan önemli halk sağlığı problemleridir (3).…”
Section: Introductionunclassified